18F-FDG PET/CT findings of intermediate bone tumors of the spine - Xianwen Hu; Peqing Yang; Tengyue Mei; Jiong Cai; Pan Wang (Scientific Reports)
Abstract Intermediate bone tumor has a certain risk of invasion and metastasis, but its invasion degree and metastasis probability are much lower than malignant bone tumor. The objective of this study was to retrospectively analyze 18F-FDG PET/CT findings in patients with spinal intermediate tumors. A total of 49 patients with spinal intermediate tumors consisting of 22 giant cell tumor of bone (GCTB), 11 osteoblastoma, 10 Langerhans cell histiocytosis (LCH) and 6 epithelioid hemangioma were subjected to evaluation using 18F-FDG PET/CT. Factors analyzed included lesion location, size, epicenter of the lesions (vertebral/posterior elements), eccentric expansile osteolysis, cortical integrity, residual bone trabeculae/spine/calcification, sclerotic rim, vertebral compression, soft tissue mass, and maximum standard uptake value (SUVmax) of lessions. GCTB, osteoblastoma, LCH, and epithelioid hemangioma showed statistically significant differences in the main body of the lesion, maximum diameter, eccentric expansile osteolysis, cortical integrity, residual bone trabeculae/spine/calcification, sclerosal margin, vertebral compression, and lesions’ SUVmax (p < 0.05). GCTB has a higher SUVmax, significantly higher than that of osteoblastoma and LCH (p < 0.05). Spinal GCTB, osteoblastoma, LCH, and epithelioid hemangioma have certain 18F-FDG PET/CT features, and 18F-FDG PET/CT may contribute to differentiate them from each other.